PROFITABILITY AND BOARD DYNAMICS: UNVEILING THEIR ROLE IN CORPORATE SUSTAINABILITY DISCLOSURE - Hubertus Ade Resha Raditya Boli; Ika Rahayuningsih (Jurnal Riset Akuntansi, 2025)
This type of quantitative research aims to investigate whether the profitability seen from ROA and board characteristics consisting of board size, board independence, and board gender diversity influences the disclosure of sustainability reporting. The sample used in this research is companies from the food and beverage sub-sector listed on the IDX during the period from 2018 to 2021, selected using the purposive sampling method. Therefore, the number of observations in this research was 124. The results of this study indicate that (1) profitability and board size have a negative and significant effect on the disclosure of sustainability reporting and (2) board independence and board gender diversity have a positive and significant effect on the disclosure of sustainability reporting.